2008
DOI: 10.1002/ch.366
|View full text |Cite
|
Sign up to set email alerts
|

Reducing and reversing pseudomemories with hypnosis

Abstract: As a forensic memory enhancement tool, hypnosis is problematic because it tends to increase pseudomemory responses and infl ate confi dence regardless of accuracy. A variety of evidence suggests that major infl uences in producing these effects are expectancy and demand characteristics. However, if expectancy and demand characteristics play a role in increasing false positive responses with hypnosis, it may be possible to use the same factors to reduce false positive responses. Some have argued that the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…However, whilst it is possible that the reductions in errors in experiments 2 and 3 may have been due entirely to the memory enhancement effects of the combined Focused Meditation/eye-closure technique, other explanations are possible. For example, a variety of evidence suggests that false memory effects can be inflated by demand characteristics and response bias effects (Murray et al 1992;Sjödén et al 2009;Smeets et al 2009;Wagstaff and Frost 1996;Wagstaff et al 2008). In such circumstances, Focused Meditation could be construed as a procedure that changes the contextual demands of the situation facilitating, or "legitimizing", resistance to misleading information and the overturning of previous spurious memory reports.…”
Section: Discussionmentioning
confidence: 98%
“…However, whilst it is possible that the reductions in errors in experiments 2 and 3 may have been due entirely to the memory enhancement effects of the combined Focused Meditation/eye-closure technique, other explanations are possible. For example, a variety of evidence suggests that false memory effects can be inflated by demand characteristics and response bias effects (Murray et al 1992;Sjödén et al 2009;Smeets et al 2009;Wagstaff and Frost 1996;Wagstaff et al 2008). In such circumstances, Focused Meditation could be construed as a procedure that changes the contextual demands of the situation facilitating, or "legitimizing", resistance to misleading information and the overturning of previous spurious memory reports.…”
Section: Discussionmentioning
confidence: 98%
“…A major concern for sociology researchers planning to use hypnosis as an autoecological tool is whether hypnosis is an effective and efficacious modality for facilitating a true and accurate recall of past events, situations and emotions. Memory retention and recall has been the subject of extensive discussion and research over many years and much still remains unclear about the psychology and neurophysiology of the hypnotic phenomenon (Wagstaff et al , 2008; Thompson et al , 2013; Waters et al , 2014; Thompson et al , 2014; Painter and Kring, 2015; Grysman and Fivush, 2016).…”
Section: Assessing the Truthfulness Of Hypnotically Evinced Autobiographical Narrativesmentioning
confidence: 99%
“…Gleaves et al (2004). Wagstaff et al (2008) and Gudjonsson et al (2014) all accept that memory recall can generate false memories and Wagstaff et al (2011) suggested that highly hypnotisable individuals might be more prone in this respect. The potential of hypnotic regression for evoking false memories of past childhood events and abuse was the subject of much contention during the 1990s and the early years of the 21st century and is one which has yet to be fully resolved (Chu et al , 1999; Green, 1999; Patihis et al , 2014; Mazzoni et al , 2014).…”
Section: Assessing the Truthfulness Of Hypnotically Evinced Autobiographical Narrativesmentioning
confidence: 99%
“…Accordingly, it seems that false memories are reduced when participants receive a hypnotic instruction that increases their vigilance about the possible presence of misleading information and their ability to distinguish such information from accurate information, in contrast with a “warning” instruction pertaining to the potential of hypnosis to engender false memories (Green et al, 1998). Thus, we suggest that it could be possible to reduce false memories by focusing participants’ attention on the events to be recalled and the potential presence of false information contained therein, rather than on explicitly manipulating participants’ expectations or beliefs about the potential negative effects of hypnosis on memory (Lindsay, 1990; Wagstaff, Brunas-Wagstaff, Cole, & Wheatcroft, 2004; Wagstaff et al, 2004, 2008). In standard experimental situations (i.e., nonhypnotic), introducing sufficiently clear and precise instructions/warnings concerning the vulnerability of memories to error reduces the number of source memory errors, if these instructions are provided prior to when misleading information is presented (Chambers & Zaragoza, 2001; Ecker, Lewandowsky, & Tang, 2010; Greene, Flynn, & Loftus, 1982; Kirsch, 1990, 1991; Neuschatz & Payne, 1996; Qin, Ogle, & Goodman, 2008).…”
mentioning
confidence: 99%